Percepatan Pemulihan Ekonomi Pasca Pandemi Covid-19 Melalui Investasi Pasar Modal Syariah - Ahmad Agus Hidayat; Achmad Fageh; Siska Arie Novita; Elissa Qathrunnada; Fahmi Akhyar Al Farabi (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
The purpose of this research is to explore and examine the strategies being pursued to achieve economic recovery after the Covid-19 pandemic through the Islamic Capital Market Investment sector. The qualitative research method used in this study through a descriptive approach. While the analysis was used by conducting a deeper discussion based on the information obtained. The research results obtained are aimed at accelerating economic recovery after the Covid-19 pandemic by strengthening the Islamic economic and capital market system, strengthening public literacy regarding investment, increasing public trust in Islamic capital market products, and strengthening regulations on Islamic capital markets.